Can different cultures think the same thoughts? : a comparative study in metaphysics and ethics - Dorter, Kenneth, 1940- (University of Notre Dame Press, 2018)
Can Different Cultures Think the Same Thoughts? studies fundamental issues in metaphysics and ethics across the major global philosophical traditions of India, China, and the West.